¿Los lugares de refugio para buques en peligro como aplicación del principio de prevención? (2017)
The objective of the article is to consider sheltered places for ships in distress as a mechanism for applying the principle of environmental prevention in the field of the oceans to prevent pollution by oil or other dangerous substances. In relation to the post 2015 Development Agenda, it has been argued that the role of the oceans should not be ignored in the next political development processes at the global level. It analyzes the particular situation of the Latin American continent and the current legal regulation of places of refuge.